Mycobacteria Isolated from Angkor Monument Sandstones Grow Chemolithoautotrophically by Oxidizing Elemental Sulfur - Kusumi, Asako; Li, Xian Shu; Katayama, Yoko (Frontiers in Microbiology, 2011)
To characterize sulfate-producing microorganisms from the deteriorated sandstones of Angkor monuments in Cambodia, strains of Mycobacterium spp. were isolated from most-probable-number-positive cultures. All five strains isolated were able to use both elemental sulfur (S0) for chemolithoautotrophic growth and organic substances for chemoorganoheterotrophic growth. Results of phylogenetic and phenotypic analyses indicated that all five isolates were rapid growers of the genus Mycobacterium and were most similar to Mycobacterium cosmeticum and Mycobacterium pallens. Chemolithoautotrophic growth was further examined in the representative strain THI503. When grown in mineral salts medium, strain THI503 oxidized S0 to thiosulfate and sulfate; oxidation was accompanied by a decrease in the pH of the medium from 4.7 to 3.6. The link between sulfur oxidation and energy metabolism was confirmed by an increase in ATP. Fluorescence microscopy of DAPI-stained cells revealed that strain THI503 adheres to and proliferates on the surface of sulfur particles. The flexible metabolic ability of facultative chemolithoautotrophs enables their survival in nutrient-limited sandstone environments.